KAJIAN 'ARKEOLOGI SITUS MASA SEJARAH' DI LASEM: PERGESERAN PUSAT KEGIATAN - Nurhadi Rangkuti (Berkala Arkeologi, 1997)
In Babad Lasem, a shift in the center of activity was recorded, which was marked by the transfer of the palace from Kriyan to Bonang-Binangun and finally to Colegawan. Two central locations of activity, namely Bonang-Binangun and Colagawan, occurred during the growing influence of Islam in the northern coastal areas of Central Java and East Java. The two central locations for these activities are in the coastal area, namely in Bonang-Binangun and Caruban. It is possible to move the location of the center of activity to the coastal area due to the increasingly busy trade during the emergence of Demak as an Islamic kingdom in the coastal area.